Preparation and Characterization of Visible-Light-Activated Fe-N Co-Doped TiO2 and Its Photocatalytic Inactivation Effect on Leukemia Tumors - Kangqiang Huang; Li Chen; Jianwen Xiong; Meixiang Liao (International Journal of Photoenergy)
The Fe-N co-doped TiO2 nanocomposites were synthesized by a sol-gel method and characterized by scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray diffraction (XRD), ultraviolet-visible absorption spectroscopy (UV-vis) and X-ray photoelectron spectroscopy (XPS). Then the photocatalytic inactivation of Fe-N-doped TiO2 on leukemia tumors was investigated by using Cell Counting Kit-8 (CCK-8) assay. Additionally, the ultrastructural morphology and apoptotic percentage of treated cells were also studied. The experimental results showed that the growth of leukemic HL60 cells was significantly inhibited in groups treated with TiO2 nanoparticles and the photocatalytic activity of Fe-N-TiO2 was significantly higher than that of Fe-TiO2 and N-TiO2, indicating that the photocatalytic efficiency could be effectively enhanced by the modification of Fe-N. Furthermore, when 2 wt% Fe-N-TiO2 nanocomposites at a final concentration of 200 μg/mL were used, the inactivation efficiency of 78.5% was achieved after 30-minute light therapy.